Prioritising patient care: The different views of clinicians and managers - Skirbekk, Helge (Nursing ethics, 2018)
Background:There is little research comparing clinicians’ and managers’ views on priority settings in the healthcare services. During research on two different qualitative research projects on healthcare prioritisations, we found a striking difference on how hospital executive managers and clinical healthcare professionals talked about and understood prioritisations.Aim:The purpose of this study is to explore how healthcare professionals in mental healthcare and somatic medicine prioritise their care, to compare different ways of setting priorities among managers and clinicians and to explore how moral dilemmas are balanced and reconciled.Research design and participants:We conducted qualitative observations, interviews and focus groups with medical doctors, nurses and other clinical members of the interdisciplinary team in both somatic medical and mental health wards in hospitals in Norway. The interviews were recorded and transcribed verbatim.Ethical considerations:Basic ethical principles for research ethics were followed. The respondents signed an informed consent for participation. They were assured anonymity and confidentiality. The studies were approved by relevant ethics committees in line with the Helsinki Convention.Findings:Our findings showed a widening gap between the views of clinicians on one hand and managers on the other. Clinicians experienced a threat to their autonomy, to their professional ideals and to their desire to perform their job in a professional way. Prioritisations were a cause of constant concern and problematic decisions. Even though several managers understood and empathised with the clinicians, the ideals of patient flow and keeping budgets balanced were perceived as more important.Discussion:We discuss our findings in light of the moral challenges of patient-centred individual healthcare versus demands of distributive justice from healthcare management.Conclusion:The clinicians’ ideals of autonomy and good medical and nursing care for the individual patients were perceived as endangered.